Factors that influence mexican youth to undertake an agribusiness - Alvarado Lagunas, Elías; Morales Ramírez, Dionicio; Ortiz Rodríguez, Jeyle (Agricultura, Sociedad y Desarrollo, 2022)
Presently, entrepreneurship has great importance, both for entrepreneurs and for public and private institutions. In Mexico, there are few studies about the decision that young people make to undertake an agribusiness. The objective of this study is to analyze the impact of individual and socioeconomic characteristics on the probability of young people deciding to undertake –specifically– an agribusiness. The study was developed in the Mexican national territory with 3213 young people. The information necessary was gathered through a questionnaire and the support from fourteen academic groups from different universities of the country; two groups were formed that are different, with young people from the North and from the South. Applying a logit type discrete binary selection model, the study concludes that men are more determined to undertake an agribusiness than women, in the national and regional scope. The North region of Mexico contrasts clearly with the South region in the decision of implementing an agribusiness project. Young people from the South have 40% more probability of starting a business of this type than young people from the North. The implications of this study serve for those interested in the promotion of entrepreneurship in the agriculture and livestock sector, government and researchers, as well as future entrepreneurs in this business model.